PERTUMBUHAN INSTITUSI SOSIAL POLITIK SAMUDERA PASAI, MALAKA, BANTEN DAN MATARAM - Iswanto, Juli (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
The journey and progress of Islam in Indonesia has finally brought about changes in social fields that are different in social construction and encourage political points of view. This development can be seen from the problems of language, teaching, and socio-government. The language change was distinguished by a change in names which were mostly taken from Arabic, such as Abdul, Syah and Malik. Moreover, the pesantren contains about sharia, tashawuf, and development organizations. The presence of Islam in Southeast Asia at that time may not have an impact on the world today. After an episode of workers' resistance in the South China region against the Chief of Hey Tsung (878-889 AD) which killed many Muslims, they began to seek asylum in Kedah (around that time Kedah was remembered as Sriwijaya territory). This paper is of a qualitative type, with a library research approach. The entry of Islam to Indonesia changed the social and political conditions based on Islam as brought by the preachers. Second, the presence of the Islamic kingdom in Indonesia had a great influence on the development and spread of Islam in Indonesia. Third Some of the Islamic kingdoms that contributed to the spread of Islam in Indonesia were the Samudera Pasai Kingdom, the Banten Kingdom, the Malacca Kingdom, and the Mataram Kingdom.